2014
DOI: 10.1038/ncomms5117
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition algorithm reveals how birds evolve individual egg pattern signatures

Abstract: Pattern-based identity signatures are commonplace in the animal kingdom, but how they are recognized is poorly understood. Here we develop a computer vision tool for analysing visual patterns, NATUREPATTERNMATCH, which breaks new ground by mimicking visual and cognitive processes known to be involved in recognition tasks. We apply this tool to a long-standing question about the evolution of recognizable signatures. The common cuckoo (Cuculus canorus) is a notorious cheat that sneaks its mimetic eggs into nests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(142 citation statements)
references
References 46 publications
3
139
0
Order By: Relevance
“…This then selects for increasingly fine-tuned discrimination by hosts (Davies and Brooke, 1989;Stevens, 2010, 2011;Davies, 2011). Such an arms-race is a canonical example of co-evolutionary processes driving both perceptual and signaling mechanisms (Davies and Brooke, 1989;Davies, 2011;Igic et al, 2012;Stoddard et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This then selects for increasingly fine-tuned discrimination by hosts (Davies and Brooke, 1989;Stevens, 2010, 2011;Davies, 2011). Such an arms-race is a canonical example of co-evolutionary processes driving both perceptual and signaling mechanisms (Davies and Brooke, 1989;Davies, 2011;Igic et al, 2012;Stoddard et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While above-threshold visual contrast is increasingly known to induce egg rejection among brood parasite hosts, it is not firmly established whether comparing own versus foreign eggs is a more reliable cue than other visual comparisons available in the host's nest environment (Endler and Mielke, 2005;Thorogood and Davies, 2013). For example, relatively few studies have examined whether and how nest lining color influences parental behavior (but see Bailey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, background color is not the only feature used in recognition, because coots reject many eggs that do not differ measurably in background color from the host's eggs. There is increasing evidence that spotting patterns may also be more important than background color in hosts of mimetic interspecific parasitic eggs (Lahti & Lahti, 2002;Stoddard, Kilner, & Town, 2014). The use of spots for egg recognition in coots could explain the seemingly paradoxical results of our mimicry experiment, whereby hosts treated all three treatments similarly despite the treatments representing a gradient of similarity in shape and background colour (Lyon & Eadie, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…These studies assess chromatic reflectance and/or pattern data to characterize how the tetrachromatic avian visual system assesses the foreign eggshell's appearance (AvilĂ©s et al 2010 ;Stoddard and Stevens 2011 ;Hanley et al 2013 ;Igic et al 2012 ;Poláček et al 2013 ;Stoddard et al 2014 ), and have repeatedly confirmed long-standing conclusions that foreign eggs are rejected more often when they are perceived as more dissimilar to the hosts' own eggs (Cassey et al 2008 ;Spottiswoode and Stevens 2010 ;Stevens et al 2013 ;Croston and Hauber 2014 ;Hauber et al 2015 ; Fig. 1 ).…”
Section: Aq4mentioning
confidence: 98%